Caesarean scar pregnancy complicated by partial rupture in the second trimester: A case report - Prakriti Garkhail; Astrid S.M. Vinkesteijn; Sabina de Weerd (Case Reports in Women's Health, 2024)
This case report examines caesarean scar pregnancy, a rare but significant complication associated with increasing global caesarean rates. It explores diagnostic challenges, therapeutic interventions, and the importance of a multidisciplinary approach. This report details the case of a patient at 13 + 4 weeks of amenorrhea presenting with severe abdominal pain, diagnosed with caesarean scar pregnancy and scar dehiscence causing major haemorrhage. Emergency surgery and interventional radiology were employed for pregnancy evacuation and haemorrhage control. This report emphasizes niche pregnancy complexities and underscores the need for evidence-based practices to mitigate maternal morbidity and mortality. Additionally, it emphasizes the need for training in niche detection by transvaginal ultrasound for all clinicians encountering patients with early pregnancies.